Serum Creatinine Distinguishes Duchenne Muscular Dystrophy from Becker Muscular Dystrophy in Patients Aged ≤3 Years: A Retrospective Study - Wang, Liang; Chen, Menglong; He, Ruojie; Sun, Yiming; Yang, Juan; Xiao, Lulu; Cao, Jiqing; Zhang, Huili; Zhang, Cheng (Frontiers in Neurology, 2017)
Here, we investigated correlations between serum creatinine levels and clinical phenotypes of dystrophinopathy in young patients. Sixty-eight patients with dystrophinopathy at the Neuromuscular Clinic, The First Affiliated Hospital, Sun Yat-sen University, were selected for this study. The diagnosis of dystrophinopathy was based on clinical manifestation, biochemical changes, and molecular analysis. Some patients underwent muscle biopsies; serum creatinine levels were tested when patients were ≤ 3 years old, and reading frame changes were analyzed. Each patient was followed up, and motor function and clinical phenotype were assessed when the same patients were ≥ 4 years old. Our findings indicated that in young patients, lower serum creatinine levels were associated with increased disease severity (p < 0.01), and that serum creatinine levels were the highest in patients exhibiting mild Becker muscular dystrophy (BMD) (p < 0.001) and the lowest in patients with Duchenne muscular dystrophy (DMD) (p < 0.01), and were significantly higher in patients carrying in-frame mutations than in patients carrying out-of-frame mutations (p < 0.001). Serum creatinine level cut-off values for identifying mild BMD [18 μmol/L; area under the curve (AUC): 0.947; p < 0.001] and DMD (17 μmol/L; AUC: 0.837; p < 0.001) were established. These results suggest that serum creatinine might be a valuable biomarker for distinguishing DMD from BMD in patients aged ≤ 3 years and could assist in the selection of appropriate treatment strategies.